2006
DOI: 10.1148/radiol.2382041905
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Organ-confined Prostate Cancer: Incremental Value of MR Imaging and MR Spectroscopic Imaging to Staging Nomograms

Abstract: Endorectal MR imaging and combined endorectal MR imaging-MR spectroscopic imaging contribute significant incremental value to the staging nomograms in predicting OCPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
115
1
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(121 citation statements)
references
References 40 publications
1
115
1
4
Order By: Relevance
“…Researchers in numerous studies have suggested that magnetic resonance (MR) imaging, used alone or in combination with functional or metabolic MR imaging techniques, such as MR spectroscopic imaging, can contribute valuable information to the pretreatment assessment of prostate cancer (4,(11)(12)(13)(14)(15)(16)(17)(18). Therefore, the purpose of our study was to prospectively evaluate the diagnostic performance of T2-weighted MR imaging and MR spectroscopic imaging in detecting lesions stratified by pathologic volume and Gleason score in men with clinically determined low-risk prostate cancer.…”
Section: Genitourinary Imaging: Mr Performance Characteristics In Lowmentioning
confidence: 99%
“…Researchers in numerous studies have suggested that magnetic resonance (MR) imaging, used alone or in combination with functional or metabolic MR imaging techniques, such as MR spectroscopic imaging, can contribute valuable information to the pretreatment assessment of prostate cancer (4,(11)(12)(13)(14)(15)(16)(17)(18). Therefore, the purpose of our study was to prospectively evaluate the diagnostic performance of T2-weighted MR imaging and MR spectroscopic imaging in detecting lesions stratified by pathologic volume and Gleason score in men with clinically determined low-risk prostate cancer.…”
Section: Genitourinary Imaging: Mr Performance Characteristics In Lowmentioning
confidence: 99%
“…With the implementation of diffusion-weighted and contrast-enhanced prostate MRI, the ability to spatially localize dominant lesions has reduced the risk of understaging and even been proposed as a criteria to omit biopsy in prostate cancer patients on active surveillance [17][18][19][20][21]. However, many significant prostate cancers detected on random biopsies fail to reveal a targetable lesion on MRI when compared to radical prostatectomy specimens [22].…”
Section: Editorialmentioning
confidence: 99%
“…MRI or combined MRI/MRSI findings contribute significant incremental value to standard prostate cancer staging nomograms for predicting organ-confined cancer and seminal vesicle invasion (69). In addition, two studies of the same patient population found that MRI results contributed significant incremental value to clinical variables in the prediction of extracapsular extension, although the difference was only significant when the images were interpreted by radiologists specializing in genitourinary MRI (65,70).…”
Section: Localization and Staging Of Clinically Significant Diseasementioning
confidence: 99%
“…However, as lymph node metastasis is rare at the time of diagnosis, the National Comprehensive Cancer Network (NCCN) guidelines recommend using CT or MRI only in patients with a nomogram-indicated probability of lymph node metastasis greater than 20%. CT and MRI both have high specificity but low sensitivity in the detection of lymph node metastases (76), as detection depends on size criteria (generally, a short-axis diameter greater than 7-8 mm), even though lymph node metastases may be present in normal-sized nodes or absent in enlarged nodes (69,77). However, the use of MRI before treatment has the advantage of allowing the primary tumor and the pelvic lymph nodes to be assessed simultaneously.…”
Section: Mri In the Pretreatment Detection Of Metastasesmentioning
confidence: 99%